2016
DOI: 10.4317/medoral.20981
|View full text |Cite
|
Sign up to set email alerts
|

Current methods of sedation in dental patients - a systematic review of the literature

Abstract: ObjetiveThe main objective of this systematic literature review is to identify the safest and most effective sedative drugs so as to ensure successful sedation with as few complications as possible.Study DesignA systematic literature review of the PubMed MEDLINE database was carried out using the key words “conscious sedation,” “drugs,” and “dentistry.” A total of 1,827 scientific articles were found, and these were narrowed down to 473 articles after applying inclusion and exclusion criteria. These 473 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
1
32
1
8
Order By: Relevance
“…This superiority can be attributed to the pharmacological sedative and anal gesic effects of dexmedetomidine. 18 In a previous study by Hall et al, the authors reported that alpha2 agonists behaved differently from other sedatives due to their unique characteristics that make their action in inducing sedation closer to normal sleep, yet obtaining the level of consciousness sufficient to respond to orders. 8 This is consistent with the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This superiority can be attributed to the pharmacological sedative and anal gesic effects of dexmedetomidine. 18 In a previous study by Hall et al, the authors reported that alpha2 agonists behaved differently from other sedatives due to their unique characteristics that make their action in inducing sedation closer to normal sleep, yet obtaining the level of consciousness sufficient to respond to orders. 8 This is consistent with the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are relevant to adult dental patients because anesthetic-related complications during dental care are similar to those reported in hospital settings, 10 and the sedation drugs administered in the included studies are used in moderate sedation in dental practices. 47 Future research should include double-blinded studies to reduce the risk of bias and improve confidence in the findings. Lastly, in this review we did not examine the effect of capnography in dental practice, especially in patients with asthma, chronic obstructive pulmonary disease, and other conditions in which exhalation may be compromised, but these topics warrant study.…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 99%
“…A recent analysis reviewed sedation modalities for dental procedures [227] applied in 12 different cohorts. Ketamine (0.25 mg/kg, 5, 6, 10, or 50 mg/kg) was used in combination with other drugs, IN (drops or spray) in 4 studies, IV in 2, orally in 5 (of which 1 patient was given ketamine-laced lollipop), and IM in 1 study.…”
Section: Inhalational Ketamine: Ketamine By Inhalationmentioning
confidence: 99%